Semiconductor Nanocrystals: Liquid–Liquid Diffusion‐Assisted Crystallization: A Fast and Versatile Approach Toward High Quality Mixed Quantum Dot‐Salt Crystals (Adv. Funct. Mater. 18/2015). (May 2015) - Adam, Marcus; Wang, Zhiyu; Dubavik, Aliaksei; Stachowski, Gordon M.; Meerbach, Christian; Soran‐Erdem, Zeliha; Rengers, Christin; Demir, Hilmi Volkan; Gaponik, Nikolai; Eychmüller, Alexander
<x xml:space="preserve">Abstract</x> Mixed crystals composed of semiconductor quantum dots are demonstrated as emissive centers and NaCl as host matrix. These composites are prepared using the liquid–liquid diffusion assisted crystallization (LLDC) approach described by N. Gaponik and team on page 2638. These mixed crystals are robust and strong emitters suitable for color conversion applications.